Relationship between venous thromboembolism and inflammatory bowel disease in Taiwan: a nationwide retrospective cohort study - Yi-Jen Fang; Hui-Hsia Hsieh; Heng-Jun Lin; Cheng-Li Lin; Wan-Yi Lee; Chi-Hua Chen; Fuu-Jen Tsai; Bang-Jau You; Ni Tien; Yun-Ping Lim (BMC Cardiovascular Disorders)
Abstract Background Inflammation significantly influences thrombosis development, with venous thromboembolism (VTE) risk linked to various systemic inflammatory diseases, but not fully established in inflammatory bowel disease (IBD). Using a population-based cohort study conducted in Taiwan, we investigated the impact of IBD on the risk of VTE, deep vein thrombosis (DVT), and pulmonary embolism (PE), as well as the impact of anti-IBD treatments. Methods A study was conducted on a cohort of patients with IBD diagnosed between 2010 and 2019 using the National Health Insurance database. The risks of VTE, DVT, and PE, as well as anti-IBD treatment use, were examined using Cox proportional hazard regression analysis. Results The overall number of person-years recorded for 12,126 patients with IBD (mean age: 49.18 years; 55.31% male) and 12,126 controls (mean age: 49.19 years; 55.31% male) was 64,057 and 72,056, with a follow-up duration for the two cohorts was 5.28 and 5.94 years, respectively. After adjusting for age, gender, and comorbidities, the adjusted hazard ratios (aHRs) of VTE, DVT, and PE in patients with IBD were 5.58 [95% confidence interval (CI) = 3.97–7.87], 5.48 (95% CI = 3.83–7.86), and 4.96 (95% CI = 2.00-12.35) times higher, respectively, than those in the control cohort. Male patients with IBD and those under the age of 50 were more likely to develop VTE (aHR = 8.54, 95% CI = 2.00-12.35; aHR = 15.75, 95% CI = 5.73–43.26, respectively). Compared to the cohort of patients with IBD receiving no treatment, patients receiving anti-IBD treatments did not show a significant change in the risk of developing VTE. Additionally, compared to the IV steroid cohort, patients with IBD who only used oral steroids had a substantially lower incidence of VTE, particularly with average doses of ≤ 80 mg (aHR = 0.24, 95% CI = 0.10–0.59). Conclusion Patients with IBD are at an increased risk of developing VTE, particularly DVT and PE. While our study found that anti-IBD treatments did not significantly alter this risk, proactive management of associated factors and close monitoring remains essential for preventing VTE in this population. Identifying and addressing specific associated factors should be prioritized in clinical practice to mitigate the heightened risk of VTE in IBD patients.